Entre document immédiat et fiction de mémoire : Histoire et enjeux du désenchantement des actualités visuelles - Émilie Houssa (Conserveries Mémorielles)
Nowadays, the immediacy of events and their retransmission prevents any hindsight of reflexive action on their performances. The present that is perpetually presented through images of information erases the ability to create a thought past of our society. Under the reign of self-presentation of information (Rancière, 1999), memory can only be built by the demonstration of a lack or overflow of information. If "memory is fiction," as many scholars claim (such as Jacques Rancière, Bernard Stiegler and Paul Ricoeur), it seems more and more difficult to set up a space and a time of fictionalisation in this stream of images experienced as the trace of a present and presented soon forgotten. The purpose of this article is to highlight the need to think this "fiction of memory" within the images of information. To do this, the author proposes to trace historically and conceptually the development of this situation through the history of images of information, by examining specifically the passage of newsreels to TV News, which marks a turning point in the imaginations of memory and information.